Nivel de conocimientos sobre los factores de riesgo y vías de transmisión de la sífilis y gonorrea en los estudiantes de los colegios La Salle y Adolfo Valarezo de la ciudad de Loja. - Merchán Castro, Leyda Narcisa (2013)
The infections of sexual transmission constitute a problem of public health, for the sequels that take place and that alone it is observed in them, as example the syphilis that serious late complications that include the neurosífilis, cardiovascular syphilis and the gonorrhea that can produce inflammatory pelvic illness takes place and to increase the risk of pregnancy ectopic. With the realization of this work it is sought to approach the knowledge of the students since Preposition the transmission roads and factors of syphilis risk and gonorrhea they are constituted in a problem at world level. The investigation type is of prospective, descriptive, traverse character that was carried out it in the schools "Adolfo Valarezo" and "The you Leave him" of the city of Loja, the universe of the present study constituted by 300 second students and third of high school, the sample belonged to 194 students; the gathering of data was carried out through the survey, the same one that allowed to determine the level of knowledge on this thematic one for the identification from the risk to those that are exposed. After carrying out the analysis and interpretation of the data, we conclude that if they have knowledge on the factors of risk and roads of syphilis transmission and gonorrhea the students object of the present investigation according to the age and sex this way: 53% corresponds to the school Adolfo Valarezo and 57% they correspond to the school the you Leave him, although the population's percentage that you/they don't know the topic exists. The information obtained by the students in relation to the topic was provided by means of conferences organized by the directive of the schools in the Adolfo's 22% Valarezo and 21% of the you leave him. The transmission roads in relation to the age and sex, 48% of the students of the school Adolfo Valarezo and 32% of the students of the school the you Leave him they point out to the sex without preservative as main infection source; followed by sex oral 20% and 14%; and transfusions sanguine 19% and 10%, respectively. Words Key: infections of sexual transmission, adolescents